Agent based modelling of electric vehicles (EV) in netlogo to mimic real life EV charging scenario at public charging stations - Su, Fabian Piao Sen (2017)
Large scale adoption of EVs undoubtedly raises electricity demand by a large extent. Hence, there is a need for comprehensive planning of charging infrastructure in order to prevent power failures or scenarios where supply exceeds demand. An essential part of this planning involves the prediction of charging demand. Charging demand is affected by several factors such as location of charging stations and pricing. In order to implement the optimum charging infrastructure, it is important to consider all the crucial factors that affect the charging load. Thus, several studies have come up with models to simulate the charging demand. However, some of the models did not include factors that deal with the social characteristics of EV drivers while others did not focus much on the economic elements. This report aims to evaluate these aspects by inculcating them in a simulation model and determining the effects of these factors. The final goal is to be able to optimize the location of the charging stations as that is one of the most fundamental factors that affects the charging load.